Results of the California Healthy Homes Indoor Air Quality Study of 2011–2013: impact of natural gas appliances on air pollutant concentrations. (17th March 2015) - Mullen, N. A.; Li, J.; Russell, M. L.; Spears, M.; Less, B. D.; Singer, B. C.
Abstract: This study was conducted to assess the current impact of natural gas appliances on air quality in California homes. Data were collected via telephone interviews and measurements inside and outside of 352 homes. Passive samplers measured time‐resolved CO and time‐integrated NOX, NO2, formaldehyde, and acetaldehyde over ~6‐day periods in November 2011 – April 2012 and October 2012 – March 2013. The fraction of indoor NOX and NO2 attributable to indoor sources was estimated. NOX, NO2, and highest 1‐h CO were higher in homes that cooked with gas and increased with amount of gas cooking. NOX and NO2 were higher in homes with cooktop pilot burners, relative to gas cooking without pilots. Homes with a pilot burner on a floor or wall furnace had higher kitchen and bedroom NOX and NO2 compared to homes without a furnace pilot. When scaled to account for varying home size and mixing volume, indoor‐attributed bedroom and kitchen NOX and kitchen NO2 were not higher in homes with wall or floor furnace pilot burners, although bedroom NO2 was higher. In homes that cooked 4 h or more with gas, self‐reported use of kitchen exhaust was associated with lower NOX, NO2, and highest 1‐h CO. Gas appliances were not associated with higher concentrations of formaldehyde or acetaldehyde.